Effects of TBEP on the induction of oxidative stress and endocrine disruption in Tm3 Leydig cells. Issue 10 (24th March 2015) - Jin, Yuanxiang; Chen, Guanliang; Fu, Zhengwei
Abstract: The flame retardant tris (2‐butoxyethyl) phosphate (TBEP) is a frequently detected contaminant in the environment. In the cultured TM3 cells (originated from ATCC), effects of TBEP on the induction of oxidative stress and endocrine disruption were evaluated. It was observed that exposure to 100 μg/mL TBEP for 24 h significantly reduced the viability of TM3 cells. The mRNA levels of genes related to oxidative stress including Sod, Gpx1, Cat, and Gsta1 were changed in a dose‐dependent and/or time‐dependent manner after exposure to 30 and 100 μg/mL TBEP for 6, 12, or 24 h. Moreover, notable decrease in glutathione (GSH) contents and increases in oxidized glutathione (GSSG) contents as well as the antioxidant enzyme activities like superoxide dismutase, catalase, glutathione peroxidase, and glutathione S‐transferase were found in the group treated with 100 μg/mL TBEP for 24 h, indicating that TBEP induced oxidative stress in TM3 Leydig cells. In addition, the expression of genes related to testosterone (T) synthesis including cytochrome P450 cholesterol side‐chain cleavage enzyme (P450scc), cytochrome P450 17α‐hydroxysteroid dehydrogenase (P450‐17α), and 17β‐hydroxysteroid dehydrogenase (17β‐HSD) and T levels in medium were remarkably declined by the treatment of 100 μg/mL TBEP for 24 h. And TBEP could inhibit the expression of P450‐17α and 17β‐HSD and T levels up‐regulated by hCG in TM3 cells. Taken together, these findings indicated that TBEP can induce oxidative stress and alter steroidogenesis in TM3 cells. © 2015 Wiley Periodicals, Inc. Environ Toxicol 31: 1276–1286, 2016.